(untitled) (Research, Society and Development, 2021)
Introduction: Class III malocclusion has skeletal and dental components that can often impair the patient’s facial appearance. Its treatment may involve orthognathic surgery or compensatory orthodontics. Case report: This case report presents a Class III malocclusion compensatory orthodontic treatment performed with the Biofunctional prescription brackets. Biofunctional prescription presents a torque value of 0° for the maxillary incisors and +10° for the mandibular incisors, which counteracts to the side effects of the use of Class III intermaxillary elastics, minimizing it, providing a more stable, aesthetic and with a healthier periodontal occlusion. Conclusion: The Class III malocclusion compensatory orthodontic treatment performed with Biofunctional prescription obtains satisfactory results, even depending on the patient collaboration with the use of intermaxillary elastics.